Impoliteness of Directive Speech Acts in Online Indonesian Language Learning - Rahmawati, Laili Etika; Hidayat, Nurul; Kurniawan, Andra (State institute of islamic studies salatiga, 2021)
This study aims to describe the impoliteness of directive speech acts in online Indonesian language learning. The data collection technique in this study used the observation, note, and record technique. The object of this research was the analysis of directive speech act impoliteness. The data analysis technique used in this study was a data triangulation model. The study results indicate an impoliteness of directive speech acts on Indonesian language learning conducted by the teacher. The teacher unintentionally performed impoliteness on the directive speech acts. The first data found that the teacher asked all the students to pay attention impolitely. The second data showed that the teacher as a speaker prohibits students from taking attendance. The third data showed that the teacher used the impolite directive speech acts when saying the utter